ECONOMY OF COVID WITH R12-R47 AS SALAT JAMAK TO HUMAN REFLEXIVITY IN FUNDAMENTAL LANGUAGE - R Mochamad A (UICELL, 2021)
This research has purpose to analyse economy in Covid age with formula of Roikhan-12 (R12) as Salat Jamak and formula of Reflexivity-47 (R47) as finished object of human in fundamental language by Quran. R12 is a simple constant in the beginning of creation. R47 is a complex structure of physical object in existing creation. These research objects are the holy book and formulas of R-12 and R-47. Research is studied through reference of books, journals, holy books, and other electronic media. The methodology uses analytical descriptive in analogies and comparative sentences in language grammar. The methods are reflexivity, similarity and hahslm 472319. The results are the analogy of R-12 as worship of Plural Pray (Salat Jamak) before R-47. R-47 is the physical conject as the existing creation in universe. Comparative sentence between ‘Not I create jin and human except for worship’ with ‘Not I create tea and coffee except for guest’. These sentences can be analogue as the mirroring system that corresponds to a projector paradigm consisting of the notebook, projector, and screen. The mirror's position consisted of shadow, mirror, and people. The blueprint presence is a reflexivity of the constant 12 stored from the Quran 51.56 verse number (1+5) times (5+6) root of digit 2 becomes 6x2=12. Twelve reflects 1 salat Subuh and 2 salat Jamak (Dzuhur Asar and Magrib Isa). R-12 can be illustrated as religion and R-47 can be illustrated as science where R-12 simple is the same with R-12* complex or R-47. This R-12 and R-47 also can be adapted to languages structures in economic covid age. Keywords: economy, covid, r12, r47, language